2019
DOI: 10.1590/2175-3369.011.e20190033
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes da adesão aos serviços de mobilidade compartilhada: uma investigação empírica no contexto brasileiro

Abstract: Resumo Os serviços de mobilidade compartilhada (SMC) são uma alternativa inovadora de transportes nos centros urbanos. Sendo assim, utilizando-se de uma survey com 597 usuários, por meio de uma análise fatorial confirmatória, identificaram-se os determinantes do uso dos SMC no contexto brasileiro. Os benefícios econômicos, o prazer e a sustentabilidade são preditores da atitude e da intenção comportamental em relação aos SMC. Notou-se um relacionamento negativo entre reputação e atitude quanto aos SMC. Observo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…Climate crises, economic uncertainties, weakened social connections, virtualization of relationships, urban and regulatory impacts, as well as issues associated with the dynamics of safety and labor benefits, among others, have been measured in a wide range of studies (Ertz & Leblanc-Proulx, 2018;Akhmedova et al, 2020;Mont, et al, 2020;Räisänen et al, 2020), and in this sense, this study sought to assess one of the prisms of this relationship, specifically, the set of indicative variables of the motivators for the use of on-demand travel modes in Brazil, considering their implications in developing markets (Santos et al, 2019;Yuana et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate crises, economic uncertainties, weakened social connections, virtualization of relationships, urban and regulatory impacts, as well as issues associated with the dynamics of safety and labor benefits, among others, have been measured in a wide range of studies (Ertz & Leblanc-Proulx, 2018;Akhmedova et al, 2020;Mont, et al, 2020;Räisänen et al, 2020), and in this sense, this study sought to assess one of the prisms of this relationship, specifically, the set of indicative variables of the motivators for the use of on-demand travel modes in Brazil, considering their implications in developing markets (Santos et al, 2019;Yuana et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The variables Boarding Convenience and Time in addition to Data Security emerge from the offer from the platforms indicating a consistent departure from the traditional way of offering this type of service, studies such as those by Liu et al, 2018;Santos et al, 2019;Ozanne & Ozanne, 2020 discuss the importance and influence of technology and its impacts on consumers.…”
Section: Valuing the Professional Reduction Of Circulating Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…urbe. Revista Brasileira de Gestão Urbana, 2022, 14, e20210111 6/20 Coelho et al,2017;Santos, et al, 2019;Vaclavik et al, 2020;Capaverde et al, 2020;Silva et al, 2018;Barreto,et al, 2021. Despite the limited volume of national publications, it is indicated that the variables are concentrated on elements such as cost, safety, technological facilitators and convenience, with a greater volume of variables appearing in the social and technological dimensions.…”
Section: Consumption Inductors Of Displacement Modes Linked To Ride-h...mentioning
confidence: 99%
“…A tabela apresenta estudos representativos internacionais dos motivadores de uso dos serviços de ride-hailing, a exemplo de HENAO;MARSHALL 2018;YUANA et al, 2019;ILAVARASAN et al,2018;GOMEZ-LOBO, 2019;LANG et al, 2020;OZANNE;OZANNE, 2020;BAJAJ et al, 2020e também nacionais, tais como COELHO et al, 2017MANN, 2018;SANTOS et al, 2019;SÁ;PITOMBO, 2019;HADDAD et al, 2019;PASQUAL et al, 2019;CAPAVERDE et al, 2020;VACLAVIK et al, 2020;SILVA et al, 2021. É possível observar que indicadores de comportamento de uso -quando da expansão inicial do modelo -vincularam-se a preocupações com questões voltadas a sustentabilidade, anseio por novas conexões, redução do consumismo, além da virtualização das relações (GEISSINGER et al, 2020;RÄISÄNEN et al;ZHU;LIU 2020;BERGER et al, 2020).…”
Section: R C Aunclassified